Pelaksanaan Konseling HIV/ AIDS oleh Bidan Pada Saat Antenatal Care di Puskesmas Wilayah Kota Bandung: Tati Rostati*) - Poltekkes Kemenkes Bandung (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2009)
Pelaksanaan Konseling HIV/ AIDS oleh Bidan pada Saat Antenatal Care di Puskesmas Wilayah Kota Bandung Tati Rostati 1 Jurusan Kebidanan Bandung E-mail : rostati_hasan@yahoo.com ABSTRACT Worldwide of human population that infected by HIV/AIDS (Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome) growth every year. Based on UNAIDS and WHO estimation, by the end of 1999 more than 34,4 million people in the world became an HIV carriers and 1,3 million from that are children less than is years old which was generated from mother to her fetus. By counseling perhaps, the pregnant mother could do voluntary early HIV/AIDS detection by checking their HIV/AIDS status. In Indonesia, HIV/AIDS counseling implementation is still not effective/optimum. That issue was supported by BKKBN study result that showed in 2002 only 2.7% of HIV/AIDS counseling implementation done by health officer and increase 15.2% in 2004. Method : This research is a quantitative research which goals is to know several factors that influence HIV/AIDS counseling implementation by midwife during antenatal care assessment at Bandung Public Health Service Center using cross sectional approach with univariate analysis and bivariate analysis to find the relationship between independent and dependent variable. Results: Statistical analysis result shows that predisposing, enabling and reinforcing factors that were studied in this research don't have significant relationship (not related with or not influencing) to HIV/AIDS counseling implementation that do by midwife's during antenatal care assessment at Bandung Public Healthy Service Center with p= 0,402; OR-0,792, enabling factor results P=0,813; OR-I ,31, reinforcing factor P= 0,797; OR=1,31respectively. Keywords : HIV/AIDS counseling, midwives, antenatal care assessment